Microencapsulation Techniques and its Role in Medicine - Promraksa, Bundit; Daduang, Jureerut; Khampitak, Tueanjit; Hongsprabhas, Pranithi; Boonsiri, Patcharee (Srinagarind Medical Journal, 2014)
Microencapsulation is a process by which core materials, e.g. drugs and natural products, are enclosed with shell materials, e.g. protein hydrolysate and phospholipids, to form microcapsule. Microcapsule size varies from 1 – 1,000 micron. The advantages of microcapsules are 1) to improve properties of the core substances, which are sensitive to light and easily oxidized, to be more stable and 2) to control the release of core materials at suitable time and concentration. Therefore, this technique is applied in agriculture, textile, food industries and especially in medicine. Microcapsule can be produced by chemical and physical methods. In medical science application, a physical method “freeze dry” is preferred. The mechanism of releasing core substances depends on enzyme, pressure or chemical reaction in the body. This technique plays role in treatment and prevention of several diseases including diabetes mellitus, cancer, cardiovascular disease, and infectious disease. Using microcapsule, cell transplantation was successful in type I diabetes patient. At present, this technique is being developed for high efficiency.